Port hinterland connectivity - Olaf Merk; Theo Notteboom (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2015)
The competitiveness of a seaport depends on the extent the cargo handled in the port can reach its hinterland destination (e.g. Acciaro & McKinnon, 2013). The importance of hinterland connections has been recognised as one of the most critical issues in port competitiveness and development in most ports around the world. Upgrading of facilities and equipment, privatization of port operations and increased sophistication of berth planning have resulted in drastic reduction of ship turnaround times over the last decade. The smoothness of port-hinterland connections has not followed at the same pace. Increasing ship vessel size - and the related emergence of maritime hubs and spokes - will only exacerbate the bottlenecks related to port hinterland connectivity. One of the main issues related to the development of adequate hinterland connections in ports is the need to coordinate multiple actors often with conflicting mandates that constitute the mêlée of private and public institutions governing port hinterland infrastructure development.
Keywords: 330; Hafenwirtschaft; Hinterland; Verkehrsinfrastruktur; Küstenschifffahrt; OECD-Staaten